All about Antarctica : a fact book about the southernmost continent - Martin, Marc (Martin, Marc. Everything & everywhere book., 2025)
"Put on your parka and snowshoes, and get ready to embark on a journey to the way, way south. You can hitch a ride on a snowcat, explore majestic icefalls, hunt for meteorites, and marvel at migrating whales--or just stay in for a movie and pizza. From colossal squid and active volcanoes to research vessels and cricket matches, there's a lot more to the South Pole than just penguins and icebergs--though there are also a lot of penguins and icebergs. Learn how humans survive in the coldest place on Earth, and discover what surprises await in this fragile and fascinating region that most will never see. All you need is a good guide and a little curiosity . . . so what are you waiting for? Let's go!"--